A Novel Design of 5.5/7.5 ghz Dual Band‐Notched Ultrawideband Antenna. Issue 12 (23rd September 2013) - Ojaroudi, Nasser; Ojaroudi, Hamed; Ojaroudi, Mohammad; Ghadimi, Noradin
ABSTRACT This article presents a new design of ultrawideband (UWB) monopole antenna with the characteristics of dual band rejection .The antenna consists of a square radiating patch with U‐shaped slot and a pair of Γ‐shaped slits, and a ground plane with an open‐circuit slit which provides a wide usable fractional bandwidth of more than 120%. By applying the open‐circuit slit in the ground plane, a new resonance at 12.1 GHz is excited and much wider impedance bandwidth can be produced. The band notching of wireless local area network (5–6 GHz), is achieved by inserting a U‐shaped slot, and a band‐notching for downlink of X‐band satellite communication systems (7.25–7.75 GHz) is obtained by embedding two Γ‐shaped slits at square radiating patch. The simulated and measured results show that the antenna design exhibits an operating bandwidth (VSWR<2) from 2.86 to 12.92 GHz excluding the rejected bands. The proposed antenna configuration is simple, easy to fabricate and can be integrated into any UWB system. The proposed antenna has a symmetrical structure which improves the antenna radiation pattern characteristics. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2910–2915, 2013